2019
DOI: 10.1016/j.jad.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Facilitated attention for gambling cues in adolescent problem gamblers: An experimental study

Abstract: Studies investigating attentional biases in gambling have observed that problem gamblers' attention is biased toward gambling cues. Despite the increase of gambling among adolescents, to date, no study has ever examined the role of attentional bias in adolescent gambling, as well as the relationships between adolescent gambling severity, craving, and alcohol use. Methods The present study comprised 87 adolescent participants. Based on South Oaks Gambling Screen Revised for Adolescents (SOGS-RA) scores, partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 82 publications
0
13
0
2
Order By: Relevance
“…However, more than half of the young respondents believed that gambling yields a high financial return on their investment [39]. In an experimental study, adolescent problem gamblers displayed greater bias towards attending to gambling-related cues that promoted the potential for financial gains than their non-problem gambling peers [81], and another study found that adolescents' attitudes towards money and distorted gambling cognitions mediated the relationship between social cynicism and fate control on gambling participation [82].…”
Section: Attitudes Towards and Reasons For Gamblingmentioning
confidence: 98%
“…However, more than half of the young respondents believed that gambling yields a high financial return on their investment [39]. In an experimental study, adolescent problem gamblers displayed greater bias towards attending to gambling-related cues that promoted the potential for financial gains than their non-problem gambling peers [81], and another study found that adolescents' attitudes towards money and distorted gambling cognitions mediated the relationship between social cynicism and fate control on gambling participation [82].…”
Section: Attitudes Towards and Reasons For Gamblingmentioning
confidence: 98%
“…So far, studies investigating attention in GD have primarily analysed reaction times or fixation times when viewing addiction-relevant stimuli vs non-addiction-relevant stimuli, known as attentional bias studies [33][34][35] . These studies have shown that increased attention to addiction-relevant cues plays an important role in the onset and the maintenance of addictive (and also gambling) behaviour [36][37][38][39][40][41][42][43] but also see 44,45 . These findings have led to the development of attentional bias modification training as interventions against addictive behaviour 46 and are currently being tested in GD 47,48 .…”
Section: Introductionmentioning
confidence: 99%
“…Así, la adolescencia o inicio de la edad adulta supone un periodo crítico o de mayor vulnerabilidad del desarrollo ya que existe una mayor experimentación con conductas de riesgo, inmadurez cognitiva y de desarrollo y sensibilidad a la presión de sus compañeros y al marketing y, por ende, un mayor riesgo de implicarse en conductas de juego problemáticas (Emond y Griffiths, 2020;Lambe et al, 2015;Sussman y Arnett, 2014). De esta forma, el trastorno del juego entre adolescentes se ha convertido en un problema de salud pública emergente (Calado et al, 2020) que continua en aumento y tiene un impacto cada vez mayor (Ciccarelli et al, 2019). La accesibilidad, las oportunidades de juego, la exposición, el empleo de una moneda virtual y su consecuente desensibilización ante las pérdidas monetarias, la temática de los juegos, la aceptación social y la percepción del juego como un entretenimiento inofensivo favorecen la expansión y la implicación de los jóvenes en las conductas de juego (Armstrong et al, 2018).…”
Section: Introductionunclassified
“…En la adolescencia el trastorno de juego se ha asociado con múltiples factores como son el género masculino (Kang et al, 2019), bajo rendimiento escolar, conducta delictiva, reiterados conflictos familiares (Caillon et al, 2012), padres jugadores, menor supervisión parental, baja autoestima, mayor consumo de alcohol, hiperactividad e impulsividad (Emond y Griffiths, 2020). También se ha relacionado con la sensibilidad a las recompensas inmediatas, estilo de toma de decisiones espontáneo inadaptado y dificultades para contemplar posibles consecuen-cias futuras (Donati et al, 2019), sesgos atencionales, distorsiones cognitivas (Ciccarelli et al, 2019), rasgos de personalidad desadaptativos (Ciccarelli et al, 2020), falta de autocontrol, impulsividad, ansiedad (Tárrega et al, 2015), elevados niveles de estados afectivos negativos y depresión , entre otros.…”
Section: Introductionunclassified